Effectiveness of a musculoskeletal injury preventive program in elite beach volleyball players: a retrospective study - Vinícius Soares Santos; Fábio Luís Feitosa Fonseca; Marco Antônio Serquiz; Leticia Amaral Corrêa; Bruno Tirotti Saragiotto; Leandro Alberto Calazans Nogueira (Universidade do Estado de Mato Grosso, 2020)
Objective: to evaluate the effectiveness of a preventive program in athletes of the elite beach volleyball. Method: this is a case series study of seventeen athletes from Brazilian beach volleyball team, between 15 and 20 years. Information about demographic and anthropometric data, and information about hours of practice and number of physiotherapy sessions were obtained in the medical records. The intervention program was performed for 12 weeks, including exercises for the joint complex of the shoulder and lower limbs. The severity of the injury and the functional tests (glenohumeral internal rotation, dynamic valgus, posterior chain flexibility, and vertical jump) was used as outcome measures. The pre and post-intervention outcome were compared. Results: the preventive program showed a low injury rate (1.37/1000 hours). The functional tests showed contradictory results in post-intervention evaluation. The left shoulder internal rotation (before=80º versus after=86º, p=0.024) and posterior chain flexibility (before=30º versus after=33,1º, p=0,090) showed improvement. There was no change in dynamic knee valgus (before p=0.305, after p=0.894) and vertical jump (before=300 cm versus after=296 cm, p=0.12). Conclusion: the preventive program performed showed a low injury rate and the functional tests do not show a significant improvement in post-intervention evaluation.